Subepithelial connective tissue graft for thin biotype gingiva on dark root non-vital tooth to enhance the aesthetic area: Case report: Subepithelial connective tissue graft untuk gingiva biotype tipis pada akar gelap gigi non-vital untuk meningkatkan area estetik: Laporan kasus - Made Talitha Suryaningsih Pinatih (Makassar Dental Journal PDGI Makassar, 2022)
Gingival biotype is described as the thickness of the gingiva in the faciopalatal or faciolingual dimension. Aesthetic is highly con-sidered in anterior teeth. A 35-year-old woman came with a complaint that the color of gingiva of her front teeth was slightly dark after root canal treatment 10 years ago. Clinical and radiographic examinations of the upper left lateral incisor showed no signs of inflammation or infection. Biotype evaluation was carried out with a calibrated UNCprobe using the transparency me-thod. Subepithelial connective tissue graft (SCTG) with tunneling technique was performed on the gingiva to thicken the gingi-va around the dark tooth root. SCTG autograft is a stable gingival graft material if the goal of surgery is to thicken the gingiva, so it remains the gold standard in areas that require esthetics.